(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
Economic science has long recognized labour productivity as an important factor of economic growth. In the uncertain conditions of increasingly fierce and complex competition, it becomes one of the key prerequisites for an adequate response to global challenges. The development of labour productivity has to be observed as a multi-dimensional process including numerous interconnected quantitative and qualitative factors, in particular human factors and technological advancement realized through investments in research and development (innovations). The analysis of labour productivity in the manufacturing industry of the selected countries, Germany and China, is performed in the context of an important influential factor – innovations, and interdependently with the economic growth of the selected countries. The research results and the conducted regression analyses indicate a superiority of German labour productivity in the manufacturing industry, which is strongly affected by considerable investments in research and development. However, the technological convergence of China as the upcoming power is increasingly important, which shows that the gap in labour productivity is decreasing, making developed countries face new challenges posed by globalization. The analysis of the interdependence of economic growth (GDP) and labour productivity in the manufacturing industry points to a positive link and the conclusion that the elasticity of the GDP to changes in labour productivity is greater in China than in Germany. Keywords: Labour productivity in the manufacturing industry, innovations, economic growth, Germany, China